Lexical innovation: cromulently embiggening a language - MacKenzie, Ian (Revista Alicantina de Estudios Ingleses, 2014)
In this article I look at the main ways of making new English words, and at the different types of neologisms this produces; consider various categories of people who coin them, including famous authors and television scriptwriters as well as anonymous nonnative speakers of English as a lingua franca, and highlight the similarities and differences in the ways they tend to coin words; consider to what extent the formation of new words by way of established processes or rules or schemas should be thought of as morphological productivity rather than individual creativity; and finally look at the processes by which neologisms can, potentially, be diffused.